INVASIVE PAPILLARY CARCINOMA OF THE MAMMA OF FELIS CATUS - Skrypka, M. V.; Telyatnikov, K. A.; Syvun, O. S. (Bulletin of Sumy National Agrarian University. The series: Veterinary Medicine, 2025)
The most common type of breast cancer is invasive ductal carcinoma, which originates from the epithelial cells of the mammary ducts and subsequently infiltrates the surrounding breast tissue. If treatment is not started in a timely manner, invasive ductal carcinoma can metastasize to other organs and tissues (Wasserman J., 2023). Breast carcinomas in situ are malignant epithelial tumors that “do not have the property of spreading beyond the basement membrane into the connective tissue base of the breast” (Chocteau F. et al., 2019). According to WHO Breast 2019, the term insitu is used to refer to non-invasive histotypes of epithelial origin: tubular carcinoma in situ (LCIS), ductal carcinoma in situ (DCIS) including the papillary subtype, and solid papillary subtype (CIS) (Sasano H. et al., 2020). This type of neoplastic lesions is often accompanied by multicentric growth in the ducts of the mammary glands. The cells lack the polarity and morphological structure characteristic of epithelial cells (Misdorp W. et al., 1999; Goldschmidt M. et al., 2011). The prognosis for recovery from breast carcinoma is poor due to the fact that the metastasis rate is from 50% to 90%, with the lungs, lymph nodes, liver and pleura being the most affected (Petrucci G. et al., 2021; Chocteau, F. et al., 2019). The life expectancy of this species of animals with malignant breast tumors depends on the degree of aggressiveness of the tumor, the chosen mastectomy method and other factors. The life expectancy with tumors up to 3 cm in diameter is from 3 to 54 months; more than 3 cm in diameter is 12 months (Viste, J. R. et al., 2002). According to other data, these figures are, respectively, 2 years; 6 months (Seixas F. et al., 2007). In accordance with the above, the management of patients with malignant breast tumors requires a detailed analysis of the characteristics of the disease, the state of the body in order to adjust the treatment regimen to control the course of the pathological process, extend the terms and improve the quality of life of the animal. Clinical study (clinical examination of animals, morphological and biochemical blood tests), chest radiography and abdominal ultrasound were performed in the conditions of veterinary medicine clinics in Odessa. Pathomorphological study of breast tumors was conducted on the basis of the research laboratory of the Department of Normal and Pathological Morphology and Forensic Veterinary Medicine, Faculty of Veterinary Medicine, Odessa State Agrarian University.